LENGUAJE, CONOCIMIENTO E HISTORIA - Montoya Sáez, José (Antigüedad y Cristianismo, 1995)
This article tries to throw some light on the relations between thought and language. We start by elucidating the question in the most general leve1 (i.e. the relations between language and theoretical thought) but we proceed (in the 2nd and 3rd parts) to discuss what constitudes our main interest: the relations of these between language and moral thought, and of both to the historical procss. The conclusions, although not realtivist in a strict sense, emphasize the peculiarity of the ties between the historical moralities and the languages in which they are expressed. (...)